2010
DOI: 10.1590/s0104-14282010005000016
|View full text |Cite
|
Sign up to set email alerts
|

Biocompósitos de matriz glioxal-fenol reforçada com celulose microcristalina

Abstract: Resumo: Glioxal pode ser obtido a partir de biomassa (como da oxidação de lipídeos) e não é tóxico ou volátil, tendo sido por isso utilizado no presente trabalho como substituto de formaldeído na preparação de resina fenólica do tipo novolaca, sendo usado como catalisador o ácido oxálico, que também pode ser obtido de fontes renováveis. A resina glioxal-fenol foi utilizada na preparação de compósitos reforçados com celulose microcristalina (CM, 30, 50 e 70% em massa), uma celulose com elevada área superficial.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
(16 reference statements)
0
10
0
1
Order By: Relevance
“…Previously, we have demonstrated that surface modification, to introduce a positive surface charge to cellulose (Scheme 1), allows cell attachment in the absence of matrix ligands (Courtenay et al 2017). Here we demonstrate the minimal level of surface modification required and combine this with modulation of the mechanical properties of the scaffold material, achieved by crosslinking with glyoxal (Ramires et al 2010), which results in formation of acetal and hemiacetal linkages upon curing (Scheme 2) (Schramm and Rinderer 2000), yielding films with increased elastic moduli depending on degree of crosslinking (Quero et al 2011).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previously, we have demonstrated that surface modification, to introduce a positive surface charge to cellulose (Scheme 1), allows cell attachment in the absence of matrix ligands (Courtenay et al 2017). Here we demonstrate the minimal level of surface modification required and combine this with modulation of the mechanical properties of the scaffold material, achieved by crosslinking with glyoxal (Ramires et al 2010), which results in formation of acetal and hemiacetal linkages upon curing (Scheme 2) (Schramm and Rinderer 2000), yielding films with increased elastic moduli depending on degree of crosslinking (Quero et al 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Glyoxal was chosen in this study as a chemical crosslinker due to its low toxicity to mammalian cells and ability to finely regulate the elastic moduli of the scaffolds (Ramires et al 2010;Wang and Stegemann 2011). Both unmodified and cationic cellulose films were cured in glyoxal solutions (1-12 wt%) to achieve films with a range of crosslinking determined by HPLC (Figs.…”
Section: Modulation Of Scaffold Properties: Crosslinkingmentioning
confidence: 99%
“…Other formaldehyde substitutes have proven to be helpful for the formation of phenolic resin with excellent properties. Among all the aldehyde-type alternatives, the role of furfural (Oliveira et al, 2008;Zhang et al, 2020), furfuryl alcohol (Cheng et al, 2018), glyoxal (Ramires et al, 2010) and vanillin (Foyer et al, 2016) should be highlighted. If readers are looking for more details on biosourced precursors to phenolic resins, we encourage them to read the following scientific literature (Sarika et al, 2020).…”
Section: Crosslinkersmentioning
confidence: 99%
“…Segundo Ramires et al (2010), as celuloses microcristalinas são materiais com elevada área superficial e altamente porosos, de forma a justificar a maior adsorção destes se comparada à polpa Kraft de Eucalyptus. Observa-se nas Figuras 10, 11 e 12 a morfologia e as dimensões das amostras de CMC 101, CMC 500 e polpa Kraft, respectivamente.…”
Section: Comparação Entre Os Materiais Celulósicosunclassified